Working Memory Structure in Children: Comparing Different Models During Childhood - Injoque Ricle, Irene (2012)
Working Memory (WM) is an active memory system responsible for the temporary storage and concurrent processing of information. Different authors have considered WM as a complex but unitary system, whereas others have suggested that the system is multidimensional. In this line, the model developed by Baddeley and Hitch (1974) is one of the most well known; it proposes two modality-specific components-the phonological loop and the visuo-spatial sketchpad-and a supervisory executive system-the central executive. This paper contributes to the debate on WM structure by investigating three groups of children of different ages and assessing different models using confirmatory factor analysis. The Working Memory Assessment Battery Test (Alloway, 2007; Injoque-Ricle, Calero, Alloway & Burin, 2011) was administered to 180 monolingual Spanish-speaking children. The three age groups consisted of 6-, 8-, and 11-year-old children (n = 60 participants per group). The results suggest that the WM structure is not uniform across the different age groups tested, showing progressive differentiation and specialization during childhood. This structure would appear to form between the ages of 6 and 8 years and become more complex as adolescence is approached.